RESPONSIBILITY RESTRICTED BY AGE IN THE COMMISSIONON SERIOUS CRIMES AND THE JURISPRUDENCE OF THE HALLS OF THE SUPREME COURTA - Oyarce Delgado, Jeannette (2019)
The national court of justice, emits enforceable and plenary accords with binding effects respect to the interpretation and application of the substantive rules and procedures. Which forms our legal order with the finally purpose of consolidate and unify the assumed criteria, in this way help predictability and legal security the justice system of our country